Pharmacokinetics of a netilmicin loading dose on the first postnatal day in preterm neonates with very w gestational age - Rengelshausen, Jens; Beedgen, Bernd; Tsamouranis, Konstantina; Mikus, Gerd; Walter-Sack, Ingeborg; Haefeli, Walter E.; Linderkamp, Otwin (European journal of clinical pharmacology, 2006)
Pharmacokinetic parameters are important for dose adjustment of aminoglycosides, but they are highly variable in neonates. In this study the pharmacokinetics of a netilmicin loading dose was investigated on the first postnatal day in preterm neonates with very low gestational age (GA).
Gesehen am 17.05.2021